Blast Loading on Model Earth Covered Magazines. - Kingery,Charles N (1978)
This report contains the results obtained from a series of high explosive tests designed to determine the blast loading on scaled models of earth covered munition storage magazines. A 1/30th scaled (non-responding) model was exposed to three charge weights (.454, .908 and 1.135 kg) and a 1/45th scaled model was exposed to a .454 kg charge weight. The objective was to determine the weight, configuration and stand-off distance for an uncovered TNT charge that would produce the pressure and impulse loading obtained from the explosion of a loaded earth covered munition magazine when placed at the side to side safe separation distance. A 1/30 scaled model exposed to a 1.135 kg hemispherical pentolite charge at a stand-off distance of 1.6m gave the best model simulation. This will scale, for a full-size test, to a hemispherical charge of TNT weighing 34,050 kg placed 47.2 m from the center line of the acceptor structures. (Author)